Duplication of the mandible in Klippel-Feil syndrome - DURMUŞ KOCAASLAN, FATMA NİHAL; ÇELEBİLER, ÖZHAN BEKİR (ELSEVIER SCI LTD, 2013)
The duplication of the mandible is an extremely rare case, which was first described by McLaughlin in 1948 as a case report of duplication of the mouth, the tongue and the mandible. Betty in 1956 and Davies in 1973 reported similar cases. The duplication of the mandible may be associated with the Klippel-Feil syndrome (KFS). A low hairline, short neck with cervical vertebral fusion and painless limitation of the head movement are the characteristic findings of this syndrome. The incidence of the syndrome varies from 1/30,000 to 1/40,000. Although autosomal recessive inheritance was suggested, no familial inheritance was found in some cases. A very rare case of mandibular duplication in association with KFS, whose duplicated mass was removed following distraction, has been reported. (C) 2012 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Klippel-Feil syndrome; Duplication of mandible